1993
DOI: 10.1203/00006450-199311000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Function in Lambs after Prolonged Oligohydramnios during Late Gestation

Abstract: ABSTRACI'. Our aim was to determine the effects of oligohydramnios during the last third of ovinc gestation on respiratory function in lambs during their first postnatal month. To induce oligohydramnios, amniotic and allantoic fluids were drained from pregnant ewes, starting at 109.0 +. 2.3 d of pregnancy (term = 148 d). In 10 lambs born at term, respiratory function was studied four times at rveeklg intervals; a group of nine lambs from normal pregnancies served a s controls. Over the 4-wk study period, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It is not surprising, therefore, that pulmonary hypopl asia persisted at birth after simul ated surgica l repair of a diaphragmatic hernia (22) . Furthermore, we sugges t that the failure of the hypoplastic lung to expand, in the absence of tracheal obstruction, is most probably the consequence of a relatively incompli ant lung and, perhaps more importantly, chest wall (23). Under these conditions, the normal resistance to lung liquid efflux offered by the upper airway (15,16) is prob ably insufficient to promote fluid accumulation and, therefore, increase lung expansion to the level required to stimulate lung grow th.…”
Section: Methodsmentioning
confidence: 96%
“…It is not surprising, therefore, that pulmonary hypopl asia persisted at birth after simul ated surgica l repair of a diaphragmatic hernia (22) . Furthermore, we sugges t that the failure of the hypoplastic lung to expand, in the absence of tracheal obstruction, is most probably the consequence of a relatively incompli ant lung and, perhaps more importantly, chest wall (23). Under these conditions, the normal resistance to lung liquid efflux offered by the upper airway (15,16) is prob ably insufficient to promote fluid accumulation and, therefore, increase lung expansion to the level required to stimulate lung grow th.…”
Section: Methodsmentioning
confidence: 96%
“…Data on fetal lung liquid volumes from other species, including humans, are not available. The end-expiratory volume, or functional residual capacity (FRC), of the air-filled lung in newborn iambs during the first postnatal month is approximately 20-25 mL/kg (Roy et al Jakubowski et al 1993;Fig. la).…”
Section: Control Of Fetal Lung Liquid Volumementioning
confidence: 99%
“…tracheo-amniotic shunt and amniotic fluid drainage) to induce a more severe LH than that induced by amniotic fluid alone. Previous studies in sheep have shown that drainage of amniotic fluid only induces a mild degree of lung hypoplasia [35,36]. At ~140 days of gestation, the ewes and fetuses were anaesthetized for implantation of fetal vascular catheters and a pulmonary artery flow probe; immediately after this, the fetuses were delivered and ventilated for two hours …”
Section: Our Recent Studies On the Neonatal Effects Of Fetal Lung Hypmentioning
confidence: 99%